2014
DOI: 10.1016/j.metabol.2013.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The associations between metabolic variables and NT-proBNP are blunted at pathological ranges: The Multi-Ethnic Study of Atherosclerosis

Abstract: Objective Under physiological conditions brain natriuretic peptide (BNP) is inversely associated with metabolic risk factors, but under pathological conditions these associations may tend to plateau. Material end methods 5597 individuals in the Multi-Ethnic Study of Atherosclerosis (MESA), 45–84 years of age, free of overt cardiovascular disease in 2000–02 and then again in 2003–05 participated in this study. Associations between NT-proBNP and BMI, blood lipids, homeostasis model of insulin resistance (HOMA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 49 publications
5
59
2
Order By: Relevance
“…Several previous studies showed important associations between N‐terminal pro B‐type natriuretic peptide and incident HF,46 atrial fibrillation,47 and subclinical cardiovascular disease 48. Ndumele et al demonstrated that N‐terminal pro B‐type natriuretic peptide is a strong predictor of incident HF in individuals with and without obesity 46.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies showed important associations between N‐terminal pro B‐type natriuretic peptide and incident HF,46 atrial fibrillation,47 and subclinical cardiovascular disease 48. Ndumele et al demonstrated that N‐terminal pro B‐type natriuretic peptide is a strong predictor of incident HF in individuals with and without obesity 46.…”
Section: Discussionmentioning
confidence: 98%
“…The association between blood lipids concentrations and glucose with NT-proBNP does not follow a linear association throughout the whole range of NT-proBNP values [7]. For NT-proBNP levels <100 pg/mL, we suggested that variations in NT-proBNP occur in response to physiological events.…”
Section: Introductionmentioning
confidence: 87%
“…Plasma NT-proBNP was measured at the Veterans Affairs San Diego Health Care System, using an ElecSys 2010 analyzer (Roche Diagnostics, Indianapolis, IN) [10,11]. Interleukin-6 (IL-6) was measured as previously described [7]. Lipoprotein particle concentration was determined at LipoScience, Inc. (Raleigh, NC) by nuclear magnetic resonance spectroscopy using the LipoProfile-3 algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in diabetic patients an increase in BNP and NT-proBNP levels may reflect proBNP accumulation that masks the linear relationship between residual active BNP and metabolic parameters, but being the result of altered cardiac processing is a valuable biomarker of early cardiac and hemodynamic abnormalities and of the inability of the heart to effectively counteract them by enhancing active BNP production. In keeping with this scenario, recent data from the Multi-Ethnic Study of Atherosclerosis (MESA) (81) have shown that when subclinical CVD develops and NT-proBNP levels rise, the inverse relationship between NT-proBNP and both BMI and insulin resistance is completely lost.…”
Section: Diabetes Complicationsmentioning
confidence: 97%